Informal Learning as a Catalyst for Adaptive and Resilient Generation Z Learners in the Age of Artificial Intelligence Disruption - Rila Hardiansyah; Helmi (Jurnal Pendidikan Usia Dini, Pendidikan Dasar, Menengah dan Umum, 2026)
The rapid advancement of artificial intelligence (AI), automation, and digital connectivity is fundamentally reshaping how knowledge is acquired, validated, and applied, particularly for Generation Z learners who have grown up as digital natives. This conceptual article examines how informal learning functions as a catalyst for building adaptive and resilient Generation Z learners amid AI-driven disruption. Through a systematic synthesis of literature on informal and self-directed learning theory, experiential and social learning theory, and recent scholarship on artificial intelligence in education, the article develops an integrative conceptual framework linking informal learning, AI-mediated learning ecosystems, and the development of resilience and adaptability. The synthesis indicates that informal learning increasingly functions as a continuum with formal education rather than a peripheral supplement, and that digital and AI-based environments expand opportunities for incidental, self-directed, and socially situated learning. However, digital fluency alone does not guarantee effective learning; resilience and adaptability emerge specifically through reflective engagement with authentic experience, social interaction, and problem-solving embedded in informal learning processes. The novelty of this article lies not in introducing a new construct, but in integrating informal learning, AI-mediated learning environments, and resilience-adaptability development into a single analytical framework tailored to Generation Z, offering a conceptual foundation for future empirical research and for higher education institutions designing learning environments that deliberately cultivate informal learning pathways alongside formal curricula.